Febuxostat and Increased Dialysis as a Treatment for Severe Tophaceous Gout in a Hemodialysis Patient - Lynda Ann Frassetto; Suzanne Gibson (Case Reports in Nephrology)
Uric acid accumulates in renal failure and is thought to be a uremic toxin—that is, higher levels of uric acid are more damaging to the kidneys. Urate crystals can precipitate in the kidney tubules, cause urate stones, and promote inflammatory changes in the renal interstitium and vascular endothelium. Uric acid is also a small non-protein-bound molecule and therefore easily dialyzable. Here, we present the case of an anuric hemodialysis patient with severe tophaceous gout who regained some renal function and whose gout burden significantly decreased resulting in marked improvement in functional status using a new gout medication, febuxostat, and increased frequency of dialysis.